Gastrocolic fistula secondary to colon cáncer - Irigoyen, Virginia; Espinosa, Gabriela; Massaferro, Gabriel; Viola, Marcelo (Cirugía del Uruguay, 2022)
The gastrocolic fistula described in 1755 by Albrecht von Haller, is defined as the abnormal communication between the generally transverse colon and the stomach in its greater curvature. Different etiologies are known, being a rare finding with few reports in the literature. We present the case of an 85-year-old patient with a history of anemia and weight loss who consulted due to fecal-like vomiting, without lower digestive transit disorders, without pain or abdominal distension with normal air-fluid noises and a nasogastric tube with fecal-like content. Tomography (fig. 1) confirmed a lesion of probable malignant aetiology of the splenic flexure of the colon fistulized to the stomach, so it was decided to perform a sectoral colectomy with primary anastomosis and subtotal gastrectomy, progressing favorably with discharge after 6 days. Pathological anatomy reports moderately differentiated adenocarcinoma of the colon with gastric involvement.